Experimental determination of configurational entropy in a two-dimensional liquid under random pinning. (12th February 2018) - Williams, Ian; Turci, Francesco; Hallett, James E; Crowther, Peter; Cammarota, Chiara; Biroli, Giulio; Royall, C Patrick
Abstract: A quasi two-dimensional colloidal suspension is studied under the influence of immobilisation (pinning) of a random fraction of its particles. We introduce a novel experimental method to perform random pinning and, with the support of numerical simulation, we find that increasing the pinning concentration smoothly arrests the system, with a cross-over from a regime of high mobility and high entropy to a regime of low mobility and low entropy. At the local level, we study fluctuations in area fraction and concentration of pins and map them to entropic structural signatures and local mobility, obtaining a measure for the local entropic fluctuations of the experimental system.